Linking biodiversity and intangible heritage: revival initiatives in Trás-os-Montes, Northeastern Portugal, Portugal promoting social and economic opportunities - Carvalho, Ana Maria (2014)
Trás-os-Montes, so called Nordeste Transmontano, is the most interior Portuguese region, far from the coastal centers of decision, characterized by marginalized communities, frequent migratory flows, faraway mountains and plateaus near the Spanish border, highly diverse landscapes, rich fauna and flora, and unique local heritage steeped in centuries of tradition and substantiated into an ancient Romance language, the Mirandese. For the last decade two different associations, FRAUGA and ALDEIA, settled in Terras de Miranda (Picote and Vimioso, Trás-os-Montes, Portugal) and led by young teams, have been involved in several initiatives, programs and funded projects aiming to promote biodiversity, sustainable use and conservation strategies, to document local knowledge and intangible heritage and to involve local partners in different tasks and projects.